2018
DOI: 10.1037/xlm0000423
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval practice makes procedure from remembering: An automatization account of the testing effect.

Abstract: The "testing effect" refers to the striking phenomenon that repeated retrieval practice is one of the most effective learning strategies, and certainly more advantageous for long-term learning, than additional restudying of the same information. How retrieval can boost the retention of memories is still without unanimous explanation. In 3 experiments, focusing on the reaction time (RT) of retrieval, we showed that RT of retrieval during retrieval practice followed a power function speed up that typically chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 51 publications
8
22
0
Order By: Relevance
“…In contrast, in our study, participants repeatedly practised paired‐associate items in a cued recall task, whereas the participants of Smith et al () repeatedly retrieved a list of items in a free recall situation. It has been demonstrated that repeated retrieval practice increases the level of automatization of recall (Racsmány et al, ). Because memories become more resistant to various disturbing effects as a result of automatization (Logan, ), we could assume that the automatization of retrieval following retrieval practice is an important protective factor against the negative effects of acute stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in our study, participants repeatedly practised paired‐associate items in a cued recall task, whereas the participants of Smith et al () repeatedly retrieved a list of items in a free recall situation. It has been demonstrated that repeated retrieval practice increases the level of automatization of recall (Racsmány et al, ). Because memories become more resistant to various disturbing effects as a result of automatization (Logan, ), we could assume that the automatization of retrieval following retrieval practice is an important protective factor against the negative effects of acute stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently demonstrated that repeated retrieval practice decreases the involvement of attentional control (Mulligan & Picklesimer, ) and of attentional control‐related brain regions (Keresztes, Kaiser, Kovács, & Racsmány, ; van den Broek, Takashima, Segers, Fernández, & Verhoeven, ) and increases the level of automatization of recall (Racsmány, Szőllősi, & Bencze, ). An important attribute of automatization is that memories become more resistant to various disturbing effects (Logan, ).…”
mentioning
confidence: 99%
“…Previous accounts primarily focused on the measure of recall accuracy to explain the testing effect in terms of recall decrement or long-term retention. However, recall speed, as a complimentary measure of memory performance, has largely been neglected (but see Keresztes et al, 2013 ; van den Broek et al, 2013 ; Racsmány et al, 2018 ), probably because combined findings of recall accuracy and speed cannot be easily accommodated with previous process-based accounts (cf. van den Broek et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, given that recall latencies reflect more purely memory strength ( van den Broek et al, 2013 ), successfully recalled phrases should be faster recalled than restudied phrases even after short delays. There is only little evidence so far on such an immediate testing effect as only few studies included recall speed ( Keresztes et al, 2013 ; van den Broek et al, 2013 ; Racsmány et al, 2018 ). We tested this prediction for the first time in action memory, expecting recall latencies to be shorter for retrieval practiced, as compared to restudied, phrases after both verbal and enactive encoding.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have stipulated that accuracy and speed processing might be accommodated through several parameters such as decision components and variability (Mueller & Kuchinke 2016;Ratcliff, Smith, Brown, & McKoon 2016). In terms of memory processing, recognition might include some retrievalbased processing (Racsmány, Szőllősi, & Bencze 2017). Specifically, RT has been negatively associated with accuracy (Robinson & Johnson 1996).…”
Section: Introductionmentioning
confidence: 99%